Edukasi Hipnosis untuk Menurunkan Nyeri Haid Pada Remaja Putri di Desa Pondok Meja - Gustina Gustina; Safitri Safitri (Jurnal Abdimas ADPI Sains dan Teknologi, 2022)
Almost all women have felt disturbances during menstruation in the form of menstrual pain (dysmenorrhea) to varying degrees, ranging from just aches in the pelvis from the inner side to extreme pain. One of the treatments of nonpharmacology is with hypnotherapy. Hypnotherapy is a method of instilling suggestion when the brain has been in a relaxed state, but it does not mean falling asleep or not being self-aware during practice. In Pondok Meja village, there are already many herbal plants available, one of which is turmeric which can be used by teenagers to overcome menstrual pain (dysmenorrhea) and there are those who have done the habit of drinking turmeric acid in overcoming this dysmenorrhea, it's just that to add it with hypnosis has never been done. The purpose of this activity is to increase the knowledge of young women in overcoming dysmenorrhea in addition to drinking turmeric acid. The method used is to conduct education about hypnosis to reduce menstrual pain then pretest and postest by asking 10 true and false questions with a < value of 50 is determined to be less good education, if the final score of > of 50 is determined Good Education. education about increasing the knowledge of young women reducing menstrual pain by hypnotherapy.  The results were that before the education of 76 young women only 23 were well-informed and 53 were poorly knowledgeable, while after education there was an increase in knowledge from 76 young women, 66 were well-informed and 10 were not good about hypnosis to reduce menstrual pain (dysmenorrhea).